Corn yield for silage and grains in different integrated crop-livestock systems - Pontes, Laíse; Tullio, Guilherme; Martins, Adriana; Moletta, José; Porfírio-da-Silva, Vanderley (Revista Ciência Agronômica, 2018)
In this study, the objective was to assess the influence of two doses of N (90 and 180 kg N ha-1, added to the winter pastures), two integrated crop-livestock systems (ICLS, with and without trees) and five positions between the tree rows, on the corn (Zea mays L.) quality and productivity, for silage and grain. Adopting the complete randomized block design, the treatments included three replicates. In 2006, following the 14 x 3 m spacing (currently with 158 trees ha-1) the trees were planted in 6 out of the 12 paddocks. While the corn was implemented during summer of 2013/2014, cattle grazing on the annual pasture was done during the prior winter, in both ICLS. Corn for silage was reaped at the R5 phenological stage, whereas for grains it was done at 176 days post seeding. For silage, the corn plants were grinded and then stocked in the experimental mini PVC silos. The silage varied slightly in quality along the positions between the tree rows. The differences observed between N levels in the  dry matter, crude protein (CP) and grain productivity are expressions of the residual effects of the winter fertilization. Silage quality was improved by the shade effect which minimized the acid detergent fiber and raised the CP, although it reduced the corn production for silage and grains by 52%. Some feasible techniques to reduce these losses are discussed.